Salvia officinalis Improves Glycemia and Suppresses Pro-inflammatory Features in Obese Rats with Metabolic Syndrome - Alsherif, Diana A.; Hussein, Mohammed A.; Abuelkasem, Suzan S. (Current Pharmaceutical Biotechnology, 2024)
Objectives: Obesity is regarded as the main cause of metabolic diseases and a core factor for all-cause mortality in the general population, notably from cardiovascular disease. The majority of people with type 2 diabetes have obesity and insulin resistance. Some evidence indicates that an individual with obesity is approximately 10 times more likely to develop type 2 diabetes than someone with moderate body weight. One of the most significant therapeutic herbs, Salvia officinalis (Lamiaceae) (SAGE), possesses potent medicinal importance. The aim of this article was to evaluate the anti-diabetic and antiobesity activity of SAGEAE against HFD-induced obesity in rats. Methods: Thirty adult albino rats were randomly divided into five equal groups: control, High-fat Diet (HFD) administrated rats, HFD +Salvia officinalis Aqueous Extract (SAGEAE) (150 mg/kg.bw.), HFD + SAGEAE (300 mg/kg.bw.) and HFD + metformin (500 mg/kg.bw.). Body weight, plasma biochemical parameters, oxidative stress, inflammatory indicators, hepatic Phosphoenolpyruvate Carboxykinase 1 (PCK1), Glucokinase (GK), brain Leptin Receptor (LepRb), Glucose Transporter-4 (GLUT4), Sirtuin 1 (SIRT1) and mRNA33-5P gene signalling mRNA levels were all assessed after 8 weeks. A histological examination of the liver was also performed to check for lipid accumulation. Results: The administration of HFD resulted in increased body weight, glucose, insulin, leptin, Total Cholesterol (TC), Triglycerides (TG), Thiobarbaturic Acid Reactive Substances (TBARS), Monocyte Chemoattractant Protein-1 (MCP1), Interleukine-6 (IL-6) and tumor necrosis factor-α (TNF- α) as well as hepatic PCK1, brain LepRb and adipose tissue mRNA33-5P gene expression. However, our findings revealed a significant reduction in adiponectin, High-density Lipoproteincholesterol (HDL-C), reduced glutathione (GSH) and Superoxide Dismutase (SOD) levels as well as the expression of hepatic GK and adipose tissue SIRT1 and GLUT4 genes. Also, administration of SAGEAE significantly normalized body weight, glucose, insulin, leptin, adiponectin, TC, TG, HDL-C, TBARs, SOD, IL-6, MCP-1 and TNF-α in plasma and liver tissue of HFD-treated rats. On the other hand, PCK1, GK, LepRb, SIRT1, GLUT4 and mRNA33-5P gene expression was enhanced in obese rats when administrated with SAGEAE. Histological and US studies support the biochemical, PCR and electrophoretic results. Conclusion: The findings imply that SAGEAE could be used as a new pharmaceutical formula in the treatment of obesity.
Keywords: GK